What is "Queer Asia?": a struggling pathway to globalizing Queer Studies in Communication. Issue 2 (3rd April 2021) - Eguchi, Shinsuke
ABSTRACT: This essay exemplifies the author's struggle with the concept of "queer Asia" as a case of the many pathways to globalize Queer Studies in Communication. During the demonstration, this essay pays attention to Audrey Yue's proposal of three methodological conditions of queer Asia; denaturalizing Asia as an area ; Asia as anchoring points ; and centralizing LGBT (Lesbian–Gay–Bisexual–Transgender) research in/about Asia . The overall goal of this essay is to advocate to create a space of possibilities to welcome scholarship about queer Asia in Communication and Critical/Cultural Studies.